Formation of model hepatocellular aggregates in a hydrogel scaffold using degradable genipin crosslinked gelatin microspheres as cell carriers - Lau, Ting Ting (2013)
Primary hepatocyte is probably the preferred cell for cell therapy in liver regeneration. However, its non-ideal proliferation capacity and rapid loss of phenotype during 2D culture compromises the quality and quantity of the transplanted hepatocytes, resulting in variable success rates of this treatment. Many studies have shown that the formation of 3D hepatocellular spheroids aids in the maintenance of liver-specific functions in hepatocytes. However, many of the methodologies employed require a sophisticated set-up or specialized equipment which makes it uneconomical to scale up for clinical applications. In this study, we have developed dual-functioning genipin crosslinked gelatin microspheres that serve as cell carriers as well as porogens for delivering the model cells and also for creating cavities. The cells were first seeded onto genipin crosslinked gelatin microspheres for attachment, followed by encapsulation in alginate hydrogel. Collagenase, MMP-9, was introduced either in the culture media or mixed with alginate precursor solution to allow microsphere degradation for creating cavities within the gel bulk. Accordingly, the cells proliferate within the cavities, forming hepatocellular aggregates while the alginate hydrogel serves as a confinement, restricting the size and the shape of the aggregates to the size of the cavities. In addition, the final hepatocellular aggregates could be harvested from the system by removing the alginate hydrogel via citrate treatment. Therefore, this versatile platform not only has the advantage of injectability and simplicity, the cellular aggregates generated are in a controlled size and shape and can be extracted from the system.